1976
DOI: 10.3758/bf03214430
|View full text |Cite
|
Sign up to set email alerts
|

Motivational specificity of the signal value of odor cues

Abstract: The performance of the laboratory rat in the enclosed maze apparatus is profoundly influenced by subject-generated cues that seem to be olfactory. The present experiment investigated the specificity of these cues. Odor cues produced by odor-donor rats placed in the startbox were ineffective determinants of the behavior of runway-trained rats when the deprivation states of these two groups differed. However, when the deprivation states of these two groups coincided, the odor cues produced by the odor-donor rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
18
1

Year Published

1979
1979
1999
1999

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 12 publications
1
18
1
Order By: Relevance
“…Specifically, Weaver and Davis reported that when both food-and water-deprived subjects were run together in one squad and reinforced with the same substance (a 32% sucrose-water solution), discriminations developed in the goal measure. However, since the procedures used by Weaver and Davis were quite different from those used earlier by Davis et al (1974) and Davis et al (1976)-that is, donors were not used to supply odor cues in the startbox and a single reinforcer was used-it is not clear why test subjects in the earlier studies failed to discriminate donors' odors when the motivational states of donors and test subjects were different.…”
mentioning
confidence: 77%
See 3 more Smart Citations
“…Specifically, Weaver and Davis reported that when both food-and water-deprived subjects were run together in one squad and reinforced with the same substance (a 32% sucrose-water solution), discriminations developed in the goal measure. However, since the procedures used by Weaver and Davis were quite different from those used earlier by Davis et al (1974) and Davis et al (1976)-that is, donors were not used to supply odor cues in the startbox and a single reinforcer was used-it is not clear why test subjects in the earlier studies failed to discriminate donors' odors when the motivational states of donors and test subjects were different.…”
mentioning
confidence: 77%
“…Davis et aI. (1974) and Davis, Prytula, Noble, and Mollenhour (1976) provided evidence that successful use of odors as cues for responding may be related to specific conditions associated with foodversus water-deprivation and/or reward. Using startboxplaced donor subjects, Davis et aI.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Their adaptive significance exceeds this simple relationship. However, the results of this experiment do not rule out the possibility that Rand N odors may have limited utilization under certain other circumstances (Davis, Prytula, Noble, & Mollenhour, 1976; Eslinger & Travis-Neideffer, Note 4). …”
Section: Discussionmentioning
confidence: 97%